Kant, Human Nature, and Climate Change - Wilson, Holly L. (Con-Textos Kantianos. International Journal of Philosophy, 2025)
Kant scholars are divided on whether Kant’s moral philosophy could be used to support moral consideration for animals. A good environmental ethics that has something of relevance to say to the threat of climate change requires that at the very least Kant can provide support for the preservation of the biosphere. We cannot get this directly out of his moral philosophy but we can get this out of his theory of human nature, not because humans are also animals, but because human beings develop technical skills that allow them to see a biosphere as a biosphere and understand the interconnected relationship between the biosphere, the geosphere, and the atmosphere which are all affected by climate change realities.  In addition, because of the natural predisposition to humanity, human beings are also oriented to benevolence and happiness. Human beings are the only species that can perceive the connection between the climate, biosphere, and geosphere and human and animal happiness. Thus, human beings are exceptional, and it is to human beings that we should look to make changes to our energy consumption habits so that we can care for the biosphere, atmosphere, and hydrosphere for the sake of maintaining a stable climate that benefits human civilization, human happiness, and also animal welfare. Kant’s reflections on the Lisbon Earthquake (1755) are seminal for understanding how he would respond to the crisis of climate change. His position is that humans must reevaluate what they consider is the appropriate approach to human happiness. We can work out an adequate environmental ethics using Kant’s theory of human natural predispositions which include animality, technical capacities, capacity for happiness, as well as the moral predisposition because human beings have reason and exercise it in these distinctive ways.